A Contemporary Conjecture for the Riemann Hypothesis (Journal of Informatics and Mathematical Sciences, 2024)
We will present two new results for the ''Dirichlet eta'' function \(S(s) =\sum\limits\limits_{n≥ 1}\frac{(-1)^{n}}{n^{s}}\) which would lead us to announce a new conjecture equivalent to that of the Rieman Hypothesis.